Moderasi Beragama: Upaya Guru Pendidikan Agama Kristen Mencegah Sikap Intoleran Pada Remaja - Meniria laoli; Leo Swastani Zai; Elieser R Marampa; Indraldo Undras (Sekolah Tinggi Teologi Ekumene Jakarta., 2023)
Intolerance is an attitude against differences between human beings. This intolerant attitude can hinder the welfare of the nation and state, which is marked by the emergence of various inter-religious and inter-cultural disputes that occur in society and in the educational environment. Therefore, researchers are interested in examining the extent to which teachers' efforts to prevent intolerance through cultivating an understanding of religious moderation. In this study, the researcher used a qualitative approach with library research, namely quoting previous research from various sources, including journal articles, books, and pdfs which supported the writing of this article. The results of the analysis of Christian religious education teachers' efforts to prevent intolerance in adolescents through inculcating an understanding of religious moderation as a subject delivered by PAK teachers with the hope of being able to foster an attitude of respect for differences both in terms of religion, race, ethnicity, between groups, culture and economic level, love the nation with all their heart, do not bring each other down and live as a democratic society.